Combination effects of herbal and western medicines on osteoporosis in rheumatoid arthritis: systematic review and meta-analysis - Kwon, Do Young; Gu, Ji Hyang; Oh, Minseok; Lee, Eun-Jung (Frontiers in Pharmacology, 2023)
Purpose: This study aimed to comprehensively review the effect of combining herbal medicine (HM) with Western Medicine (WM) compared to WM alone on bone mineral density (BMD) improvement for osteoporosis in patients with rheumatoid arthritis (RA). Methods: Randomized controlled trials (RCTs) were searched using 10 databases, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, and Nation Information by NII. We selected studies that used BMD as an evaluation index and administered HM treatment for osteoporosis in patients with RA. Subsequently, a meta-analysis was conducted using BMD as a continuous variable using RevMan version 5.4. Results: Eighteen RCTs that met the eligibility criteria of this study were selected. The total number of study participants was 1,491 (481 men and 1,010 women). The mean age of participants was 52.4±7.4 years, and the mean morbidity period of RA was 6.8±1.3 years. In all studies, disease-modifying anti-rheumatic drugs (DMARDs; 16 RCTs) or bisphosphonates (two RCTs) were used as WM co-intervention with HMs (17 types of HM, 18 RCTs). Overall, the combination of HM and WM improved the BMD score, producing better results than WM alone. In particular, when HM was used in combination with DMARDs, which were used in most studies, BMD improved by 0.04 g/cm² (95% confidence interval [CI]: 0.03–0.05, p<0.001, I2=19%) in the lumbar spine and 0.03 g/cm² (95% CI: 0.02–0.03, p<0.001, I2=0%) in the femoral neck compared to the DMARDs alone group after treatment. In addition to BMD, bone markers and inflammatory indicators evaluated by each RCT showed significant improvement after HM plus WM treatment. In the analysis of frequently prescribed HMs, the BMD after treatment was higher by 0.04 g/cm² (95% CI: 0.03–0.04, p<0.001, I²=45%) in the Xianlinggubao-capsule plus methotrexate (MTX) group and by 0.02 g/cm² (95% CI: 0.00–0.03, p=0.04, I²=0) in the Hanbikang-tang plus MTX group compared to the MTX alone group. Conclusion: This systematic review cautiously provides evidence for the combined therapeutic effect of HM and WM for osteoporosis in patients with RA. However, well-designed, large-scale clinical trials are necessary before recommending this combination therapy for osteoporosis in patients with RA.